Learning style and learning strategies - John Robottorn; Pat Paterson (Association for Learning Technology, 1995)
Two important factors need attention when contemplating how and where to use the new computer-based learning technologies. Firstly, in order to select the right kind of software, it is necessary to have a clear picture of the desired outcomes of a particular learning situation. There are many varieties of interactive multimedia available, and matching the tool to the job should be an early consideration. Of equal, if not greater importance, is the question of whether, for a particular learner, interactive multimedia is the most appropriate learning tool. If there is too great a mismatch between the learning styles and strategies of a particular learner and the given learning environment, learning may be inhibited rather than enhanced.